Numerical modelling of fluid flow and macrosegregation in a continuous casting slab with asymmetrical bulging and mechanical reduction. (October 2019) - Guan, Rui; Ji, Cheng; Wu, Chenhui; Zhu, Miaoyong
Highlights: A multiphase model combining microstructure, segregation and deformation is built. The asymmetrical bulging profile has a stronger effect on the centerline segregation. A greater reduction applied before solidification end can reduce macrosegregation. The heavy reduction is an effective method to further reduce macrosegregation. Abstract: The various influence factors of macrosegregation are complex and have been researched widely due to their undesirable effect on continuous casting slab. Based on an Eulerian approach, a multiphase solidification model combining turbulent fluid flow, heat transfer, microstructure evolution, solute transport with back diffusion and shell deformation were developed in this work to investigate the fluid flow and macrosegregation in continuous casting slabs under the effects of shell bulging and mechanical reduction. In this model, five phases of the slab were considered: the liquid phase, inter-dendritic melt phase of equiaxed grains, solid phase of equiaxed grains, inter-dendritic melt phase of columnar dendrites, and solid phase of columnar dendrites. The predicted temperature, shell thickness and solute element distribution were verified by the results of thermal infrared imaging, nail-shooting experiments, macrostructure analysis, and carbon-sulphur analysis. In this model, the asymmetrical bulging between two adjacent supporting rollers was considered, and its effect on the fluid flow and macrosegregation of the slab was investigated. The calculation results show that the positive centreline segregation considering the asymmetrical bulging profiles was more serious than that considering the regular sinusoidal shell profiles. Using this model, the slab macrosegregation was investigated with different reduction mechanisms in the mushy zone; a large reduction applied just before the solidification end could significantly reverse the flow of solute-enriched melt and reduce the macrosegregation. These results were also verified by an industrial application.